Electronic music in the perspective of semiotics - Humięcka-Jakubowska, Justyna (Interdisciplinary Studies in Musicology, 2018)
The aim of the present article is to describe the unique idiom of electronic music in the perspective of semiotics. The starting point of this reflection is an attempt at a definition of what electronic music is. It then moves on to questions concerning the explanation of the two main concepts of semiotics, sign and meaning. Here, the goal is to outline the general tendencies in interpreting these concepts in the context of Pierce’s theory of sign and in the context of other concepts utilized in the field of narratology, i.e. diegesis and mimesis; with the aim of transferring these interpretations to the field of electronic music. The important nodes of this reflection are illustrated with specific examples of electronic musical works. The article also explores the semantic and cognitive attributes of electronic music and the relationships between them. The understanding of meaning in electronic music is explained in terms of analogies between the characteristics of cognitive processing of the sounds of everyday life and sounds utilized in electronic music.